A study on ZnO/GaN and ZnO/PGaN structures for optoelectronic applications via SILVACO TCAD - Mohd Hassan, Nur Sabrina; Abd Rahim, Alhan Farhanah; Mohd Razali, Nurul Syuhadah; Radzali, Rosfariza; Mahmood, Ainorkhilah; Hamzah, Irni Hamiza; Muhammad, Zuraida; Packeer Mohamed, Mohamed Fauzi (Universiti Teknologi MARA Cawangan Pulau Pinang, 2025)
The integration of metal oxide materials with semiconductor substrates has emerged as a promising strategy to enhance the performance of optoelectronic devices. However, studies focusing on zinc oxide (ZnO) embedded directly onto porous gallium nitride (PGaN) remain limited. This work aims to investigate the optoelectronic performance of ZnO on both GaN and PGaN substrates using SILVACO TCAD tools. ZnO layers with varying thicknesses (0.1 μm, 0.5 μm, and 1.0 μm) were simulated on GaN and two different pore diameters of PGaN (0.5 μm and 1.0 μm). Device structures were constructed and characterised for their dark current, illuminated current, and current gain. Results indicate that while the ZnO/GaN configuration exhibits higher photocurrent, the ZnO/PGaN structures demonstrate significantly enhanced current gain up to 12 times higher than non-porous counterparts. Notably, ZnO on 0.5 μm PGaN showed a higher photoresponse than that on 1.0 μm PGaN, highlighting the influence of pore diameter. It must be added that increasing the ZnO thickness led to improved photocurrent gain across all configurations. These findings suggest that both pore diameter and ZnO thickness critically influence the optical performance of ZnO/PGaN-based photodetectors.